2018
DOI: 10.1080/16066359.2018.1498846
|View full text |Cite
|
Sign up to set email alerts
|

Testing daily associations between impulsivity, affect, and alcohol outcomes: a pilot study

Abstract: Background: Considerable research has examined impulsivity between individuals, but less research has focused on whether impulsivity fluctuates within a person. Although previous research supports trait levels of impulsivity as a risk factor for increased alcohol involvement, it is unclear whether daily (i.e., state) fluctuations in impulsivity coincide with same-day drinking behaviors. The present pilot study tested (1) the extent to which impulsivity fluctuates within-person; (2) the influence of daily impul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Both our approach, as well as the approaches of Ahn and Vassileva [ 34 ] and Stamates, Linden-Carmichael, Preonas, and Lau-Barraco [ 11 ], should be included in future studies of craving and relapse in longitudinal and real-time studies of both non-treatment seeking and clinical populations, as well as in population-level risk triage. The prevailing approach is often to use screening tools such as the Alcohol Use Disorder identification test (AUDIT) or CAGE to identify subjects at risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both our approach, as well as the approaches of Ahn and Vassileva [ 34 ] and Stamates, Linden-Carmichael, Preonas, and Lau-Barraco [ 11 ], should be included in future studies of craving and relapse in longitudinal and real-time studies of both non-treatment seeking and clinical populations, as well as in population-level risk triage. The prevailing approach is often to use screening tools such as the Alcohol Use Disorder identification test (AUDIT) or CAGE to identify subjects at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive functions also need to be assessed as state dysfunctions indicated by high-frequency assessments in longitudinal designs through different forms of digital symptom mapping and phenotyping, in line with the research of Stamates et al [ 11 ]. Because within-subject variability in impulsivity indicates higher risk levels than between-subject variability, future multimodal and multilevel model approaches, paired with machine learning techniques, may enable us to analyse when the risk is expressed (state), rather than just who is at risk (trait).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important debate in the literature concerns whether emotions ought to be conceptualised along dimensions of valence and arousal [ 40 , 41 ] or as discrete entities [ 42 , 43 ]. In the alcohol literature, the first approach, where researchers measure mood scores (e.g., PANAS, [ 38 ]) as an average of various adjectives related to either negative or positive emotions (e.g., [ 27 , 44 46 ]), has been more commonly utilised. Yet, an alternative approach, which adopts a discrete model of emotions, analyses each affect item individually.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in many clinical and preclinical studies, impulsivity is a vulnerability trait for SUD and a property of SUD [ 236 , 237 , 238 ]. Moreover, variability in impulsivity could increase the odds of both heavy drinking and alcohol-related problems [ 239 ], and a significant relationship between impaired response inhibition or impulsivity and high-risk alcohol use in nonclinical populations was demonstrated [ 240 ]. Bozkurt and colleagues [ 241 ] found that—among others—self-reported trait impulsivity predicted alcohol use severity in treatment-seeking patients [ 242 ].…”
Section: Hsd Evokes Behavioural Predictors Of Drug Of Abusementioning
confidence: 99%